Standards, Trade and Competition in the Emerging Global Information Infrastructure Environment. - David, P; Steinmueller, W (1996)
Decentralized construction of the Global Information Infrastructure (GII) is substituting market-driven, 'de facto' standards and voluntary agreements on standards for technical compatibility, in place of the engineering decisions once made by public (and quasi-public) telecommunications network operators. Due to strategic economic behaviours on the part of private businesses and national governments, the goal of a fully interoperable GII remains elusive. The Internet does not offer an entirely credible alternative model, as the standards that have facilitated its explosive growth also are contributing to serious congestion problems, and the solutions proposed point to the Internet's re-integration into the public switched telecommunications network. Technical standards will shape the GII's implications for international trade and competition, and thus raise important, but inadequately recognized issues for regulation, competition and trade policy.